Peningkatan Keterampilan Berpikir Kritis dan Sikap Kemandirian Belajar Siswa Melalui Model Pembelajaran Radec (Read, Answer, Discuss, Explain, Create) Materi Indonesiaku Kaya Budaya di Kelas IV SDN 1 Bantarsoka - Ratna Dewi Anggraeni; Badarudin Badarudin (Departement of Mathematics Education, 2024)
The learning model used in 21st century teaching must be able to provide the development of several skills. These include problem-solving, decision-making, critical thinking, understanding information and communication technology, creative thinking, communication and collaboration, and essential skills for living in society, both domestically and internationally. The RADEC learning model is an active learning model that is quite supportive of student learning success. This research was conducted using the classroom action research (PTK) model. The class action research was conducted over two periods, generally contained in two cycles. The research was conducted using the RADEC model in each lesson. The stages of classroom action research in several cycles include planning, implementation, observation, and reflection. The results stated that the use of RADEC model can improve students' critical thinking. This improvement is evident with an average score of 69 and a percentage of completeness of 48.34% in cycle I and an increase in the average score of about 88.83 and 96.67% in cycle II. The use of the RADEC model also increased student learning independence, where the average student learning independence increased to 4.243 in cycle II with very good learning independence criteria, previously there were only 3.466 students with good student learning independence criteria